Multiple Antibiotic Resistance Index of Escherichia coli Isolates from Dumai Sea Waters Riau Province - Mardalisa Mardalisa; Feliatra Feliatra; Nursyirwani Nursyirwani (Berkala Perikanan Terubuk, 2021)
The pattern of antibiotic consumption by the community which is carried out independently without medical guidance causes antibiotic pollution has reached sea waters, one of its impacts on the nature of bacterial resistance. This study aims to look at the pattern of antibiotic sensitivity to E coli that isolated from Dumai sea waters. E coli isolates that grown on MHA media were tested based on the Kirby Bauer disk diffusion method. Seventeen isolates were identified, among which a high rate of resistance to penicillin, isoniazid and streptomycin (17), a high rate of resistance to chloramphenicol (5), intermediate susceptibility to chloramphenicol (11) and only 1 sensitive to chloramphenicol. The multiple antibiotic resistance (MAR) index of E coli isolates was 0.82. These show that antibiotics like penicillin, isoniazid, streptomycin and chloramphenicol were not suitable antibiotic for E coli infection treatment. The community is expected to be more disciplined in using antibiotics and to be careful in using the Dumai sea for fishery activities